Winged bean an alternate to soybean - R., Omprakash Gobu; Bisen, Prashant; Banjara, Tej Ram; Tantuway, Girish (Indian Farming, 2018)
Winged bean is similar to soybean in both use and nutritional content. The winged bean seeds are just as good as soybean in quantity and quality of its protein, when combined with corn. Winged bean has the protein value of milk and can adequately nourish a proteinstarved infant. The nutritive quality of cooked bean as estimated by protein to efficiency ratio and net protein utilization values compares well with soybean. Like soybean, winged bean seeds contains edible oil (mostly unsaturated) that is rich in Tocopherol (Vitamin E) (some varieties even have levels higher than those of soybean and corn oils), leaving behind protein-rich flour suitable for making bread or cereals. Winged bean oil not only contains acceptable amounts of unsaturated fatty acids (especially Linoleic acid) but in contrast to soybean oil (56%), the content of Linolenic acid is quite low (39 to 42%), giving winged bean to oil the advantage of greater stability.